Про свою работу в детской книге: Из кн. "Про свою работу": [Рассказы: Для сред. и ст. шк. возраста] / А. Ф. Пахомов - Пахомов Алексей Федорович (Дет. лит., 1982)
Экземпляры: (20170413) / Инвентарный номер: 7837 / Цена: 2.00 / Сис.шифр: 76С2(Пахомов) / Авт.знак: П21 / ББК: 85.15